Non arrendersi all’ovvio. Considerazioni sugli stereotipi di genere in margine alla sentenza della Corte costituzionale n. 131 del 2022 sull’attribuzione del cognome (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Considerazioni introduttive - 2. Stereotipi e luoghi comuni - 3. Stereotipi e linguaggio di genere - 4. Contro un automatismo discriminante: la sentenza della Corte costituzionale n. 131 del 2022 - 5. Non arrendersi all’ovvio.Resist the obvious. Some considerations on gender stereotypes following the sentence of the Italian Constitutional Court, n. 131 of 2022, on the attribution of the surnameABSTRACT: The aim of this contribution is to examine the gender inequalities issues, particularly those of women, within the linguistic perspective. In particular, it highlights the discriminating capacity of stereotypes and discusses their performative dimension. Nowadays, despite several recommendations to reduce the gender gap, women continue to be marginalised in a still strong masculine culture, also through discursive practices. So, commonplaces, thanks to their simplicity and immediacy, reinforce an order of power relations between genders that place women in a position of subordination. In order to subvert this situation and reach an equal condition, the law also appears useful. The last sentence issued by the Italian Constitutional Court, on the attribution of surname to children, offers a good example in this sense. The path still appears long and uncertain, but highlighting stereotypes distortions can contribute to achieving an equal democracy which finds in inclusiveness an indispensable basis for an authentically democratic condition of life, that encourages the emergence and spread of a way of being more open, and also more ethical, a way of being of the future and for the future.